Contrast and Assimilation Effects on Task Interest in an Academic Learning Task - Bosch, Jannis; Wilbert, Jürgen (Frontline Learning Research, 2017)
Information on social comparison is one of the major factors used to evaluate academic achievement. The presence of Big-Fish-Little-Pond (BFLP) and Basking-In-Reflected-Glory (BIRG) effects of academic achievement on the self-concept have been extensively researched in various observational studies. Recent research suggests that these effects can also be transferred to motivational variables such as task interest. This paper uses an experimental paradigm to take a closer look at the mechanisms expected to be behind BFLP and BIRG effects: contrast and assimilation effects of task performance. The analyses are based on N = 129 primary education students who completed a computer-based learning task. During this task, participants received social comparative feedback that was experimentally manipulated based on 2x2 conditions: social position (high vs. low) and peer performance (high vs. low). Task interest was measured both before the start of the learning task and after it was finished. Results indicate a positive influence of high social position and high peer performance on the development of task interest from pre- to post-test compared to the low social position and peer performance conditions. Further, the hypothesized positive association between self-concept, task interest and performance in the academic learning task could also be shown.